Complications Associated With Midline Incision for Insertional Achilles Tendinopathy. (December 2020) - Hörterer, Hubert; Baumbach, Sebastian Felix; Oppelt, Sonja; Böcker, Wolfgang; Harrasser, Norbert; Walther, Markus; Polzer, Hans
Background: The midline-incision trans-achillary approach (MITA) is frequently used for addressing all pathologies of insertional Achilles tendinopathy (IAT). The aim of this study was to assess the complication rate and possible influencing factors following a MITA for IAT treatment. Methods: Presented is a retrospective cohort study with current follow-up. Patients treated surgically by a MITA, addressing all pathologies of IAT, between January 2010 and October 2016 at a single reference center with at least 12 months of follow-up were included. General demographics (age, sex, and body mass index), medical history, surgical details (individual and sum of pathologies addressed), and duration of in-hospital stay were assessed. Patient satisfaction, shoe conflict, current employment status, time to return to sports, and type of sports were recorded using a custom questionnaire. Standard statistics, chi-square, and t tests were performed using SPSS. A total of 118 patients (follow-up, 63.4%) with a mean age (± SD) of 50 ± 12 years and a mean final follow-up time (± SD) of 4.2 ± 2.1 were included. Results: Fourteen percent of patients had a minor complication, the majority (75%) of which were surgical site infections. Forty-one percent were limited in their shoe selection, and 32% reported a shoe conflict. Seventy-eight percent were very satisfied, and 89% would recommend the surgery. Neither the individual surgical procedures, their sum, nor any other parameter showed a significant influence on the complication rate. The only factor negatively affecting patient satisfaction was a shoe conflict ( P < .001). Conclusion: The MITA for IAT treatment showed a moderate minor complication rate with good midterm patient satisfaction. However, the approach might predispose patients to shoe conflict, which negatively influences their satisfaction. Level of Evidence: Level IV, retrospective cohort study.